Participation of Multifunctional RNA in Replication, Recombination and Regulation of Endogenous Plant Pararetroviruses (EPRVs) - Richert-Pöggeler, Katja R.; Vijverberg, Kitty; Alisawi, Osamah; Chofong, Gilbert N.; Heslop-Harrison, J. S. (Pat); Schwarzacher, Trude (Frontiers in Plant Science, 2021)
Pararetroviruses, taxon Caulimoviridae, are typical of retroelements with reverse transcriptase and share a common origin with retroviruses and LTR retrotransposons, presumably dating back 1.6 billion years and illustrating the transition from an RNA to a DNA world. After transcription of the viral genome in the host nucleus, viral DNA synthesis occurs in the cytoplasm on the generated terminally redundant RNA including inter- and intra-molecule recombination steps rather than relying on nuclear DNA replication. RNA recombination events between an ancestral genomic retroelement with exogenous RNA viruses were seminal in pararetrovirus evolution resulting in horizontal transmission and episomal replication. Instead of active integration, pararetroviruses use the host DNA repair machinery to prevail in genomes of angiosperms, gymnosperms and ferns. Pararetrovirus integration – leading to Endogenous ParaRetroViruses, EPRVs – by illegitimate recombination can happen if their sequences instead of homologous host genomic sequences on the sister chromatid (during mitosis) or homologous chromosome (during meiosis) are used as template. Multiple layers of RNA interference exist regulating episomal and chromosomal forms of the pararetrovirus. Pararetroviruses have evolved suppressors against this plant defense in the arms race during co-evolution which can result in deregulation of plant genes. Small RNAs serve as signaling molecules for Transcriptional and Post-Transcriptional Gene Silencing (TGS, PTGS) pathways. Different populations of small RNAs comprising 21–24 nt and 18–30 nt in length have been reported for Citrus, Fritillaria, Musa, Petunia, Solanum and Beta. Recombination and RNA interference are driving forces for evolution and regulation of EPRVs.